Strategic planning in the museums - Parseyhan, Beste Gökçe (Istanbul Kultur Univ, Atakoy Campus, Bakirkoy, Istanbul, 34156, Turkey, 2018)
Strategic planning has entered into the literature towards the end of the 20th century and gained great importance. Along with the globalization, the increase in competition has necessitated strategic planning Today, almost every institution seemsto have made strategic planning The starting point of the work is on the strategic planning in non-profit organizations. The main reason for the elaboration of the museums from non-profit organizations is that there is a limited number of studies on the subject in the literature. Michael Porter's value chain analysis has been emphasized in the stdudy conducted with literature review management. The importance of strategically determining the values in the museums has been examined. As a result, the obstacles in strategic planning are rankes and teh roles of leaders are summarized.
Keywords: Museum management; strategic planning; strategic management; value chain analysis